The Wetland Book I: Structure and Function, Management, and Methods (Springer Netherlands, 2018)
The Wetland Book is a comprehensive resource aimed at supporting the trans- and multidisciplinary research and practice which is inherent to this field. Aware both that wetlands research is on the rise and that researchers and students are often working or learning across several disciplines, The Wetland Book is a readily accessible online and print reference which will be the first port of call on key concepts in wetlands science and management. This easy-to-follow reference will allow multidisciplinary teams and transdisciplinary individuals to look up terms, access further details, read overviews on key issues and navigate to key articles selected by experts.